Modeling of the network reconfiguration considering electric vehicle charging load - Wan Izzat Aiman, Abdul Manan; Azrin, Saedi; Mohamad Heerwan, Peeie; Mohd Shahrin, Abu Hanifah (Institute of Electrical and Electronics Engineers Inc., 2021)
The new electrical motor used as the automotive engines seen to be very efficient which use only clean energy generated as one of the efforts to minimize the carbon emissions. The high usage of electric vehicle around the world for responding to the demands of taking care the ecological system has establish many Electric Vehicles (EV) charging station to accommodate the user. However, high charging loads of fast charging stations result in increased peak load demand, reduced reserve margins and voltage instability. Thus, the optimal distribution network reconfiguration with interconnection of charging station is this solution for this issue. The finding of the optimal reconfiguration in this study are used to improve the voltage profile and minimize the power loss of the distribution system. The best reconfiguration is searched by using Cuckoo Search Algorithm (CSA). The result of the finding then will be verified by comparing to other research papers for its efficiency of the method used.